2017
DOI: 10.1097/prs.0000000000003683
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Frequency, and Nature of Surgeon-Reported Conflicts of Interest in Plastic Surgery

Abstract: If self-reporting of conflicts of interest is assumed to be accurate, the number of surgeon-reported conflicts of interest in plastic surgery declined overall. Although the absolute number of consultantships did not change, the rate of consultantships rather than direct research support increased over this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This finding was consistent across all regions and suggests a possible redistribution of industry transactions away from educational endeavors within plastic surgery. 5 There are a couple of limitations of our study that warrant consideration. First, the documentation of the database depends on reporting by industry and physicians, and thus has the potential to be inaccurate.…”
Section: Ementioning
confidence: 94%
See 1 more Smart Citation
“…This finding was consistent across all regions and suggests a possible redistribution of industry transactions away from educational endeavors within plastic surgery. 5 There are a couple of limitations of our study that warrant consideration. First, the documentation of the database depends on reporting by industry and physicians, and thus has the potential to be inaccurate.…”
Section: Ementioning
confidence: 94%
“…This finding was consistent across all regions and suggests a possible redistribution of industry transactions away from educational endeavors within plastic surgery. 5…”
mentioning
confidence: 99%
“…5 Researchers who are consultants, hold stock options, or receive royalties from companies, are much more likely to report positive results. 5,20 Not surprisingly, industry is notoriously reluctant to publish negative findings. 5,21 Some trial protocols include a provision for review of the manuscript by the funder before submission for publication, and the right to delay or even veto its publication.…”
Section: Industry Payments To Professional Societies and Journalsmentioning
confidence: 99%
“…Industry payments, which may be viewed as kickbacks, have created serious legal difficulties for physicians. 2 Lopez et al 20 found that self-reported COIs have declined in recent years, but the proportion of consultantships has increased.…”
Section: Consultantsmentioning
confidence: 99%
“…14 Although consulting payments to plastic surgeons have increased in number, self-reported conflicts of interest have decreased over time. 15 According to the Centers for Medicare & Medicaid Services Open Payments Database (OPD), in previous years, consulting fees have constituted only a small percentage of the total number of industry payments made to all physicians (1.6% in 2013, and 1.2% in 2014), but were the third largest payment group in monetary value (16.1% in 2013, and 14.4% in 2014). 16,17 Many studies have analyzed relationships between industry and physicians in various subspecialties.…”
mentioning
confidence: 99%